Faktor-Faktor yang Mempengaruhi Kelelahan Kerja pada Perawat di RS Baiturrahim Kota Jambi Tahun 2025 - Dhella Adelia (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Work fatigue is an important issue that can affect nurses' performance, safety, and the quality of health services in hospitals. This study aims to identify factors associated with work fatigue among nurses at Baiturrahim Hospital Jambi City in 2025, focusing on length of service, work stress, and work shifts. This study applied a quantitative approach with a cross-sectional design. The population consisted of all nurses at Baiturrahim Hospital Jambi City, totaling 105 people. Sampling was conducted using the total sampling technique, but only 88 respondents met the inclusion criteria, as 17 nurses were excluded for not having night shifts during the study period. Data were collected through a structured questionnaire and analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed that length of service was not significantly associated with work fatigue (p = 0.473), and work stress was also not significantly associated with work fatigue (p = 0.953). In contrast, work shifts were significantly associated with work fatigue (p = 0.000). These findings indicate that work shifts, particularly evening and night shifts, contribute significantly to nurse fatigue, while length of service and work stress were not dominant factors in this study. It is recommended that the hospital management pays attention to proportional work shift arrangements, provides sufficient rest periods, and implements regular job rotations. Furthermore, nurses are encouraged to maintain physical and mental health through stress management, healthy lifestyles, and effective use of rest time to minimize fatigue risks.